Science strategy of the African Astronomical Society (AfAS): An outcome of the Science Business held in synergy with the IAUS 356. Issue Volume 15:Issue S356(2019) (October 2019) - Leeuw, Lerothodi L.; Govender, Kevin; Takalana, Charles M.; Randriamanakoto, Zara; Mamo, Alemiye
Abstract: Presented here, is a summary of discussions at African Astronomical Society (AfAS) Science Business Meeting, Addis Ababa, Ethiopia, 10-11 October 2019. This summary was deliberated with delegates of the International Astronomical Union (IAU) Symposium 356, during a lunch session of the meeting.